Survey of physical layer security of intelligent reflecting surface-assisted wireless communication systems - Hancheng LU; Yazheng WANG; Dan ZHAO; Tao LUO; Jun WU (Tongxin xuebao)
To meet the demand of high spectrum and energy efficiency in future wireless communication systems, intelligent reflecting surface (IRS), a promising technology has attracted significant attention.By proper design of IRS, PLS can be boosted from different perspectives.Based on that, current research about IRS-assisted PLS enhancement from various aspects, e.g., information-theoretic secrecy, covert communication, secret key generation and so on, were summarized.The system features and key solutions of the related papers were reviewed and several future research directions were discussed.